PENGARUH SOSIALISASI, PEMAHAMAN DAN KESADARAN, TERHADAP KEMAUAN MEMBAYAR PAJAK TERKAIT PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 (Studi Kasus Pada Pelaku UMKM di Kota Surakarta) - Enjang Setiyawan; Sugiarti Sugiarti; Eko Madyo Sutanto (Riset Manajemen dan Akuntansi, 2020)
This study aims to determine the effect of Socialization, Understanding, and Awareness of Tax Paying Will Regarding PP No. 23 of 2018. The population in this study is the UMKM taxpayers who are registered at the Pratama Surakarta Tax Office (KPP). The research data used primary data obtained by distributing questionnaires to the UMKM compulsory registered at Surakarta Primary Tax Office (KPP) using the purposive sampling method. The analysis technique used in this study uses descriptive statistics, validity, reliability, classic assumption tests, and multiple regression tests. The results showed that the socialization, understanding, and awareness had a positive effect on the willingness to pay taxes related to PP No. 23 of 2018 at the Pratama Tax Office (KPP) Surakarta.